Photo‐identification confirms polyandry in loggerhead sea turtles. (19th January 2022) - Papafitsoros, Kostas; Dimitriadis, Charalampos; Mazaris, Antonios D.; Schofield, Gail
Abstract: While polyandry in sea turtles is indicated through multiple‐paternity analyses of offspring, confirmed observations of the same female mating with multiple males are extremely challenging to obtain. To contribute to this discussion, we analysed a long‐term photo‐identification database (>20 years) of adult male and female loggerhead sea turtles frequenting the breeding area of Zakynthos, Greece, Mediterranean. A total of 38 records of mating individuals within and across seasons were assimilated via field surveys and citizen science records between 2003 and 2020. For one female, we recorded it mating with two different males within a 5.5‐h interval on the same day in 2015. This observation constitutes the first direct evidence of polyandry in sea turtles, in addition to highlighting the potential for photo‐identification to contribute information on less well‐known aspects of sea turtle biology, such as validating outputs of genetic studies.